Saudi Crane Collapse Masjid al-Haram (Lack of Safety) - Ali Gul, Fahad; Ali, Chauhdry Mehr (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study provides a national profile of major work safety accidents in Masjid al-Haram, There have been many major incidents during the Hajj over the years, causing the loss of thousands of lives. 1, intended to provide scientific basis for prevention measures and strategies to reduce major work safety accidentsand deaths.